Analisis Pengaruh Motivasi Kerja, Lingkungan Kerja, Dan Gaya Kepemimpinan Terhadap Kinerja Pegawai di Bidang Sumber Daya Air (SDA) Pada Kantor Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Alor - Gorang, Alvonso Fanisius (Jurnal Ilmiah Wahana Pendidikan, 2025)
The purpose of this study is to determine the effect of Work Motivation, Work Environment, and Leadership Style on employee performance in the Water Resources (SDA) Sector at the Public Works and Spatial Planning Office of Alor Regency. This study used a saturated sample with 18 respondents. Data analysis in this study used instrument tests, classical assumption tests and multiple linear regression analysis using the SPSS 22 for Windows calculation tool. Based on the results of the multiple linear regression test data analysis in this study, it is known that the significance value is 0.000. Thus it can be concluded that the results of this study accept Ha and reject HO which states that together the Work Motivation, Work Environment and Leadership Style variables have a significant and simultaneous effect on the Employee Performance variable in the Water Resources (SDA) Sector at the Public Works and Spatial Planning Office of Alor Regency.